ESTUDO COMPARATIVO ENTRE ARGAMASSAS DE ASSENTAMENTO PADRÃO E ARGAMASSAS COM SAIBRO - Tabarelli, Vanessa Mafra; Roedel, Tamily (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present work has as general objective to make a comparative experimental study of the standard trace of the mortar (cement, lime and sand), with the trait containing addition of gravel. The research had a quantitative approach, exploratory method and type of bibliographic and experimental research. In the experimental research, a comparative study was carried out, in which three specimens of three different mortar traces were tested: two with clay and one with cement, lime and sand, in order to verify their characteristics. The applied methods were granulometric analysis, the definition of the trace, the preparation of the mortar, the determination of the consistency content, the molding of the specimens, the determination of the water absorption by capillarity, the tensile strength in the bending and the compression. The results obtained were satisfactory when the use of the gravel in the mortars of settlement, it can be noticed in the trace with clay and without lime, the smaller amount of water absorbed. The standard trait obtained the highest resistance, but all the traces reached the values established by the NBR.